Are admission systolic blood pressures predictive of outcomes in patients with spontaneous intracerebral haemorrhage after aggressive blood pressure management?. (June 2015) - Inamasu, Joji; Oheda, Motoki; Hayashi, Takuro; Kato, Yoko; Hirose, Yuichi
<x xml:space="preserve">Abstract</x> Objective High blood pressure (HBP) is observed frequently in patients with spontaneous intracerebral haemorrhage (SICH). Although HBP at admission has been associated with poor outcomes, most studies from which such conclusions were derived had been carried out decades earlier, when aggressive BP management was not implemented. In our institution, SICH patients showing HBP undergo aggressive BP management by intravenous nicardipine with target systolic BP (SBP) less than 140 mmHg. We investigated whether responsiveness to intravenous nicardipine, haematoma expansion rate and activity of daily living 90 days after admission differed by the degree of admission SBP. Patients and methods A retrospective study was carried out by reviewing charts of 120 SICH patients admitted within 6 h of onset who were quadrichotomized on the basis of SBP: <140 mmHg (n=6), 140–184 mmHg (n=49), 185–219 mmHg (n=38) and ≥220 mmHg (n=27). The six patients with SBP less than 140 mmHg were excluded, and demographic and outcome variables of the latter three groups were compared. Whether plasma catecholamine levels differed among the three groups was also investigated. Results Optimal BP management (target SBP<140 mmHg) within 2 h of arrival was achieved in 98%, haematoma expansion occurred in 7% and the 90-day mortality rate was 11%. Responsiveness to intravenous nicardipine, haematoma expansion rate and activity of daily living were not significantly different. Furthermore, plasma catecholamine levels did not differ significantly. Conclusion The lack of difference in the demographic and outcome variables in SICH patients managed by aggressive treatment to normalize the BP indicates that the previously reported association between HBP at admission and poor outcomes needs to be re-evaluated.